Effect of Photoperiod on Growth and Reproduction of Cyclops varicans G. O. Sars, 1863 (Cyclopioda – Copepoda ) - Al-Doori, Maysaloon L.; Al-Doori, Nibrass L. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The species Cyclops varicans G.O.Sars (Which was recorded for the first time in Iraq ) was chossen to study the effect of photoperiods on the species reproduction growth . The chossen photoperiods were 0:24 , 12: 12 , and 24 : 0 L.D. The data showed obvious statistical effect of photoperiods specially 24 : 0 L.D. on the mean of clutch size , produced eggs , no. of nauplei , transformation time of nauplius I to copepodid I and transformation time of copepodid I to adult stage . The data also showed uneven effects of photoperiods on the number and maturation period of both males and females . Temperature , transparency , PH , and electrical conductivity also have been studied for the adoption as ideal condition in the laboratory for the growth and reproduce of this species .